Predicting the Blood Sugar using Machine Learning Approach - V.Ramalingam, V.; Pandian, A.; Manikandan, K.; Mega Samala Roobanvaikundaraja, Neela; ., .; ., . (International Journal of Engineering and Technology, 2018)
Background/Objective: This study is performed for predicting the blood sugar level by machine learning classifier techniques and identifies the best techniques among the techniques. Diabetes mellitus known as Diabetes caused due to increase in the blood glucose level. This will be impacting the pancreas and will be affecting the body beta cells. The beta cells play the major role in converting the glucose into energy. If the blood glucose remain undiagnosed for longer tenure, can cause various health complications like cardiovascular diseases neuropathy, nephropathy, organ failures and Eye disease. Diagnosing the sugar level in the earlier stage can help to prevent and control the health issues and save our life. Methods/Statistical Analysis: There are many classifiers already available in the computerized system. This analysis is to compare and identify the best classification technique between the classifier techniques like Naïve Bayes (NB), Decision Tree (DT), Support Vector Machine (SVM), Classification and Regression Tree (CART), K – Nearest Neighbour (K-NN) and C5. Findings: In 2017 the International Diabetes Federation had anticipated that 50% of the people in the world with the age group of 20 to 79 are not worried about their Diabetes and not aware that they may be impacted by Diabetes in near future. It also explained that 76.5% of Diabetic patients are from very low-income countries. These are not yet diagnosed if you really speaking that they don’t know that they have Diabetes. So, there is a need to diagnose and monitor the diabetes to support and help them to cure it. Keeping that in mind there are various classification techniques used to predict the diabetes. The main objective of this study is to make a comparative study and identify the best classifier which is consistent among the various datasets. The datasets used for this comparative study is University of California, Irvine machine learning repository (UCI) and PIMA Indian Diabetes Dataset. Application/ Improvements: In this study, the R-Studio application tool is used for developing and comparing the classifiers.